Procedural Aspects of Admissibility of Evidence in Criminal Proceedings - Juozapavičius, Audrius; Leonaitė, Erika (Teisė, 2021)
The article examines different models relating to procedural aspects of inadmissibility of evidence, identifies the main features and drawbacks of the Lithuanian model, and provides suggestions for its improvement.